Geographic information system based project monitoring system - Chong, Katherine Wee Tyng, 1986-; Mohamad Ghazali Hashim; Fakulti Geoinformasi dan Harta Tanah; Fakulti Geoinformasi dan Harta Tanah (2010)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2010